DNA damage and oxidative stress responses of mussels Mytilus galloprovincialis to paralytic shellfish toxins under warming and acidification conditions - Elucidation on the organ-specificity - Braga, Ana C. (2021)
Commonly affected by changes in climate and environmental conditions, coastal areas are very dynamic environments where shellfish play an important ecological role. In this study, the oxidative stress and genotoxic responses of mussels (Mytilus galloprovincialis) exposed to paralytic shellfish toxin (PST) - producing dinoflagellates Gymnodinium catenatum were evaluated under i) current conditions (CC: 19 degrees C; pH 8.0), warming (W: 24 degrees C; pH 8.0), acidification (A:19 degrees C; pH 7.6) and iv) combined effect of warming and acidification (WA: 24 degrees C; pH 7.6). Mussels were fed with G. catenatum for 5 days, and to a non-toxic diet during the following 10 days. A battery of oxidative stress biomarkers and comet assay was performed at the peak of toxin accumulation and at the end of the post-exposure phase. Under CC, gills and hepatopancreas displayed different responses/vulnerabilities and mechanisms to cope with PST. While gills presented a tendency for lipid peroxidation (LPO) and genetic damage (expressed by the Genetic Damage Indicator - GDI), hepatopancreas seems to better cope with the toxins, as no LPO was observed. However, the mechanisms involved in hepatopancreas protection were not enough to maintain DNA integrity. The absence of LPO, and the antioxidant system low responsiveness, suggests DNA damage was not oxidative. When exposed to toxic algae under W, toxin-modulated antioxidant responses were observed in both gills and hepatopancreas. Simultaneous exposure to the stressors highlighted gills susceptibility with a synergistic interaction increasing DNA damage. Exposure to toxic algae under A led to genotoxicity potentiation in both organs. The combined effect of WA did not cause relevant interactions in gills antioxidant responses, but stressors interactions impacted LPO and GDI. Antioxidant responses and LPO pointed out to be modulated by the environmental conditions in hepatopancreas, while GDI results support the dominance of toxin-triggered process. Overall, these results reveal that simultaneous exposure to warming, acidification and PSTs impairs mussel DNA integrity, compromising the genetic information due to the synergetic effects. Finally, this study highlights the increasing ecological risk of harmful algal blooms to Mytilus ganoprovincianis populations.